Paul Celan and Osip Mandelstam: Poetry under the Critique of Language - Kotelevskaya, Vera (Literatūra, 2020)
The dialogue of Paul Celan, a reader and translator, with the poetry and the whole complex poetic views of Osip Mandelstam demonstrates an important general condition: both poets worked in the context of the modernist language crisis and language critique. Mandelstam takes on the task of creating a pure language of poetry in the struggle against the symbolist “code,” in the “resurrection” of words (V. Shklovsky) by means of a “defamiliarizated” intermixture of meanings and contexts, in intentional semantic oblivion and, among other things, by immersing himself in foreign languages (“An alien speech will be my warming ear husk”). Paul Celan’s work, under the conditions of “poetry after Auschwitz” (T. Adorno), aiming at clearing up the German language of the terror of history, was influenced, among other things, by his strategy of creating a non-figurative, hermetic poetry language comparable to the so-called “absolute music” (K. Dahlhaus). This paper identifies the common poetic motifs in the works of Celan and Mandelstam, as well as individual solutions for overcoming the lingual crisis.
Keywords: Mandelstam; Celan; language critique; modernist poetry; poetology; comparative poetics